Perjalanan Menuju Pekan Olahraga Nasional 2024 (Studi Portofolio Atlet Selancar Angin) - Sefiani, Nabila; Sujarwo, Sujarwo; Sari, Eka Fitri Novita (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study explores the journey of a windsurfing athlete in preparing for the XXI National Sports Week (PON) Aceh–North Sumatra 2024. Using an autoethnographic approach, it examines the technical, mental, and infrastructural challenges faced by the athlete, as well as the role of nutrition, sleep, and social support in enhancing performance. The findings reveal that adapting to the new iQFoil equipment is a major challenge, requiring mastery of new techniques. Balanced nutrition and quality sleep play a crucial role in maintaining stamina and recovery, while support from coaches, family, and sponsors significantly contributes to motivation and mental resilience. However, limited training facilities and the lack of high-quality domestic competitions remain significant obstacles to windsurfing development in Indonesia. This study recommends improving infrastructure, organizing high-quality domestic competitions, and providing internationally certified coaching programs to enhance athlete development. With long-term investment in infrastructure and training programs, Indonesia has the potential to produce world-class windsurfing athletes.